Analysis on the differences in volatile components of different typical base liquor of sauce-flavor Baijiu based on GC-IMS - LIAO Fengmei, CHEN Renyuan, YANG Xueli, ZHAO Cheng, LI Xiaobo, YU Fangqiang, WANG Ye, ZHANG Hanren, WU Xinying (Zhongguo niangzao)
In order to explore the quality characteristics of sauce-flavor (Jiangxiangxing), alcohol-sweet, Jiaodi typical base liquor in sauce-flavor Baijiu, the volatile components of the three typical base liquor were visually analyzed by gas chromatography-ion migration spectrometry (GC-IMS). Combined with principal component analysis (PCA), orthogonal partial least squares-discriminant analysis (OPLS-DA), fingerprint and relative odor activity value (ROAV), the differences of volatile components in different typical base liquor were investigated. The results showed that a total of 35 volatile components were detected in the three typical base liquor, including 16 esters, 10 aldehydes and ketones, 4 alcohols, 2 acids, 1 furan and 2 others. There were differences in the volatile components of the three typical base liquor. According to P<0.05, variable importance in the projection (VIP) value and relative odor activity value (ROAV), 3 key differential compounds (VIP>1, ROAV>1, P<0.05) were obtained, which were ethyl 3-methylbutyrate, butyraldehyde and hexanal, respectively. The research results provided a basis for analysis of volatile aroma characteristics of different base liquor of sauce-flavor Baijiu and a valuable reference for distinguishing the quality of different typical base liquor.